Dimethoxycurcumin Acidifies Endolysosomes and Inhibits SARS-CoV-2 Entry - Khan, Nabab; Afghah, Zahra; Baral, Aparajita; Geiger, Jonathan D.; Chen, Xuesong (Frontiers in Virology, 2022)
The pandemic of coronavirus disease 2019 (COVID-19) caused by infection by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) continues to take a huge toll on global health. Although improving, currently there are only limited therapies against SARS-CoV-2. Curcumin, a natural polyphenol, exerts antiviral effects against a wide variety of viruses and can inhibit SARS-CoV-2 entry. However, undesirable physicochemical and pharmacokinetic properties of curcumin limit its clinical application. Here, we determined the effects of dimethoxycurcumin (DiMC), a methylated analog of curcumin with improved bioavailability, on the entry of SARS-CoV-2. DiMC blocked entry of pseudo-SARS-CoV-2 into Calu-3 human non-small cell lung adenocarcinoma cells and Vero E6 green monkey kidney epithelial cells. Mechanistically, DiMC acidified lysosomes, enhanced lysosome degradation capabilities, and promoted lysosome degradation of angiotensin converting enzyme 2 (ACE2), a major receptor for SARS-CoV-2 entry, as well as SARS-CoV-2 and the SARS-CoV-2 S1 protein. Furthermore, other lysosome acidifying agents, including the TRPML1 agonist ML-SA1 and the BK channel activator NS1619, also blocked the entry of pseudo-SARS-CoV-2. Thus, the anti-SARS-CoV-2 potential of DiMC and lysosome acidifying agents might be explored further as possible effective therapeutic strategies against COVID-19.